Case Study: Finance for sustainable agricultural intensification - Dalberg Asia (Commission on Sustainable Agriculture Intensification, 2021)
To meet the growing demand for food in the Global South in a sustainable manner, current funding in innovation for sustainable agriculture intensification will need to be increased exponentially. New financing instruments will play an important role in increasing the overall funding for sustainable agriculture. Not only are current levels of funding inadequate, but also many existing investment instruments are not designed to cater to the high-risk potential and below market-rate return of agricultural funding and solve for market failures in specific sub-sectors or technologies. Thus, only large funders such as governments or institutional private investors make up the bulk of the funding towards agricultural innovation and SAI. While philanthropic funding from large multilaterals and bilaterals has the potential to fill the gap, grant and traditional debt finance does not provide a long-term sustainable solution to fund agricultural innovation. Hence, to fill the funding gap, new financing instruments are required that can attract mainstream investors at scale and fund a wider range of agricultural innovation enterprises and institutions.